Risk factors for stunting incidents and positive deviance behavior of mothers towards toddlers in the stunting locus village - Nurul Maqfira; Budi Setiawan; Cesilia Meti Dwiriani (AcTion: Aceh Nutrition Journal, 2024)
Stunting is a growth disorder during infancy that is caused by prolonged malnutrition. The research aims to analyze risk factors for stunting in toddlers and identify positive deviance behaviors of mothers in stunting locus villages. Research using a cross-sectional design was carried out in Tompo Village, Barru Regency in September-November 2023 with a sample size of 83 toddlers and 8 mother informants. Data collection was done through interviews and Focus Group Discussion. Statistical analysis includes Chi-Square, Mann-Whitney Test and logistic regression with 95% Cl. Analysis of positive deviance behavior data using data reduction, data display, conclusion drawing and presented in narrative. The results of the study showed that there were 3 variables that were risk factors for stunting, namely maternal height during pregnancy <150 cm (p=0,007;OR=5,294), mothers with less nutritional knowledge (p=0,009;OR=8,267) and not receiving exclusive breastfeeding (p=0,027;OR =4,797). The conclusion of this study is that the mother's height during pregnancy, nutritional knowledge, and exclusive breastfeeding are risk factors for stunting. The positive deviance behaviors of mothers found were carrying out early initiation of breastfeeding, exclusive breastfeeding, providing complementary foods and early introduction of animal protein according to WHO recommendations and prioritizing children in food distribution.